ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY - Ula, Ma’rifatul; Hidayat, Solikhul (JURNAL FAIRNESS, 2021)
Timeliness of financial statements can be seen from the Audit Delay, the period between the closing date of the book and the date of the auditor's report. The purpose of this study is to analyze the effect of firm size, liquidity, profitability, solvency, and audit opinion on audit delays individually (partial), and simultaneously (simultaneously) on audit delays in banking companies listed on the Indonesia Stock Exchange in 2015 - 2017.The data used are secondary data taken from the financial statements of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2017 period obtained from the website www.idx.co.id. The sample of this research is 33 companies from 43 banking companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling method. The data analysis technique used is descriptive statistics, classical assumption test and multiple linear regression analysis.The results of the study show that the variables of Firm Size, Profitability, Solvency and Audit Opinion have no effect on Audit Delay and the Liquidity variable has a negative effect on Audit Delay. While the results of the F test show that Company Size, Liquidity, Profitability Solvency and Audit Opinion have an effect on Audit Delay in Banking Companies listed on the Indonesia Stock Exchange in 2015 - 2017.